INFLUENCE OF SUGAR BEET PLANT THICKNESS ON ITS DISEASES - I. Sulaymonov; A. Khabibullaev (Galaxy International Interdisciplinary Research Journal, 2023)
Sweetness of the leaf and root of sugar beet leads to severe damage by various insects. The reduction of damage to the plant is primarily directly related to the number of its seedlings. The distribution of sugar beet diseases is also directly related to the number of seedlings. therefore, the number of seedlings for sugar beet is important. In the conditions of Andijan region, it is advisable to plant in the 60X25-1 system so that the number of seedlings is normal.